(untitled) (Altre Modernità, 2015)
Mrs Dalloway is probably the most multifaceted and complex novel by Virginia Woolf; this complexity derives from the writer’s desire to represent life seen both from the points of view of the insane and the sane: “the world seen by the sane and the insane side by side” (D2, 14 ottobre 1922, p. 207). The novel, thus, is structured on two main plots, whose protagonists are Mrs Dalloway on one side (representing the ‘sane truth’) and the veteran Septimus Warren-Smith on the other (representing the ‘insane truth’). During one single day, the stories of the protagonists develop without intersecting in the city of London. In such a complex design, the window becomes a strong symbol of communication and connection between these two worlds which only seem to be detached and independent. Not only that, but since the beginning of the novel the window symbolises also the passage from a time frame to another, from the present moment to a more or less distant past, thus permitting the author to linger on the past of the characters, revealing aspects of their personalities that, otherwise, would remain unknown. This essay then will present the symbology of the window in Virginia Woolf’s novel through the analysis of the most effective episodes of Mrs Dalloway, where this object becomes a mean of communication between apparently disconnected realities like sanity and madness, youth and adulthood, past and present and life and death.